2018
DOI: 10.1088/1361-6455/aac8a1
|View full text |Cite
|
Sign up to set email alerts
|

Laser photoexcitation of Rydberg states in helium with n > 400

Abstract: Helium atoms travelling in pulsed supersonic beams have been photoexcited from the metastable 1s2s 3 S 1 level to Rydberg states with principal quantum numbers exceeding 400 by resonanceenhanced two-colour two-photon excitation using narrow-bandwidth CW laser radiation. To achieve this, the photoexcitation region was shielded and stray electric fields cancelled using a cubic arrangement of 80mm×80mm copper plates. The excited Rydberg atoms were detected by pulsed electric field ionisation downstream from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…These electrodes were separated by 13 mm. The Rydberg states were prepared using a resonance-enhanced two-photon excitation scheme, with UV and IR laser beams [27]. The UV laser was frequency stabilized to be resonant with the 1s2s 3 S 1 → 1s3p 3 P 2 transition at 25 708.587 6 cm −1 (≡ 388.975 1 nm).…”
Section: Methodsmentioning
confidence: 99%
“…These electrodes were separated by 13 mm. The Rydberg states were prepared using a resonance-enhanced two-photon excitation scheme, with UV and IR laser beams [27]. The UV laser was frequency stabilized to be resonant with the 1s2s 3 S 1 → 1s3p 3 P 2 transition at 25 708.587 6 cm −1 (≡ 388.975 1 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Drift rates as low as 2 µV cm −1 h −1 have also been measured [70]. Such measurements could be performed independently using a co-electrometry with a different species [69,70]. For a field of 30 µV cm −1 , the quadratic Stark effect is dominant for s-states, and measurements with 10 Hz uncertainty should be possible up to n = 23, with n ≈ 40 accessible if the stray field is determined to 1 µV cm −1 .…”
Section: A Improved Measurementsmentioning
confidence: 90%
“…However other experiment have shown that stray fields can be reduced to the 30 µV cm −1 level by performing electrometry with high-n states (n > 100) [68,69]. Drift rates as low as 2 µV cm −1 h −1 have also been measured [70]. Such measurements could be performed independently using a co-electrometry with a different species [69,70].…”
Section: A Improved Measurementsmentioning
confidence: 99%
“…At the position between these electrodes where their separation in the x dimension was 19 mm the atoms were prepared in the |n = 55, = 54, m = +54 ≡ |55c circular Rydberg state using the crossed fields method [46,47]. To implement this, laser photoexcitation was carried out in the presence of perpendicular pulsed electric and static magnetic fields of regions of the electromagnetic spectrum [48]. After photoexcitation the electric field was switched off adiabatically to transfer the atomic population into the |55c state as indicated in Fig.…”
Section: Interferometry Schemementioning
confidence: 99%